Impact of Technical and Vocational Education and Training on ABCD Approach in Nepal - Giri, Raj Bahadur (Journal of Training and Development, 2025)
Technical and Vocational Education and Training (TVET) aims to equip individuals with skills that are in demand and likely to remain relevant in the long term, promoting economic sustainability. Asset-Based Community Development (ABCD) seeks to build on local assets and capacities, creating solutions that are sustainable because they are rooted in the community itself. TEVT and ABCD both support holistic development connecting effective framework, paying particular attention to social cohesion, economic resilience, and community empowerment. The findings underscore the pivotal role of TVET courses in equipping individuals with employable skills and talents, enabling them to actively drive transformative changes within their communities. By fostering entrepreneurship, expanding livelihood opportunities, and strengthening social networks, TVET programs significantly contribute to inclusive development outcomes, spur economic growth, and facilitate poverty reduction. However, the integration of TVET into the ABCD framework faces substantial challenges, including limited funding, socioeconomic disparities, and legal restrictions, which hinder its effective implementation. Despite these obstacles, there remains significant potential for innovation, collaboration, and legislative enhancement to address these issues and optimize the benefits of TVET for community development. In essence, this article examines into the intricate ways in which Technical and Vocational Education and Training (TVET) is woven into Nepal's Asset-Based Community Development (ABCD) paradigm. This includes integration of TVET within the ABCD paradigm holding the considerable promise for fostering community.